A Sustainable Raw Material for Phytocosmetics: The Pulp Residue from the Caryocar brasiliense Oil Extraction - Pegorin Brasil, Giovana Sant’Ana [UNESP]; Borges, Felipe Azevedo [UNESP]; Machado, Amanda de Andrade [UNESP]; Mayer, Cassia Roberta Malacrida [UNESP]; Udulutsch, Renata Giassi [UNESP]; Herculano, Rondinelli Donizetti [UNESP]; Funari, Cristiano Soleo [UNESP]; dos Santos, André Gonzaga [UNESP]; Santos, Lucinéia [UNESP] (My University, 2022)
Agroindustrial residues have great potential to improve sustainable production and generate high value-added chemical products. The Cerrado is considered the most threatened biome in Brazil, which houses 4600 endemic species, such as Caryocar brasiliense Cambess., Caryocaraceae. Its fruit, popularly known as “pequi,” is used in regional culinary, in the treatment of diseases, and its consumed portion corresponds to only 10% of its weight. In this work, a “pequi” pulp residue extract was prepared and incorporated in a cosmetic formulation. Both were chemically characterized, and their antioxidant and sun protection factor activities were assessed, as well as the in vitro toxicity in red blood cells and fibroblasts. The extract and the phytocosmetic presented high levels of phenolic compounds, which were identified by liquid chromatography, and showed antioxidant and photoprotective activities that can be justified by the presence of well-known antioxidant compounds. In toxicological tests, both samples exhibited low toxicity in the hemolysis assay (rates < 5%) and low cytotoxicity (viability > 100%). Thus, the extract from C. brasiliense pulp residue presents great potential to be explored in the development of cosmetic products. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Agroindustrial residue; Antioxidant; Chromatography; Phenolic compounds; Photoprotector